Evaluasi Instalasi Pengolahan Air Limbah Industri Tepung Tapioka PT Sari Tani Sumatera, Serdang Bedagai - Amir Husin; Muhammad Faisal; Trisno Utomo Naibaho (Jurnal Serambi Engineering, 2022)
PT Sari Tani Sumatera uses the WWTP system in method stabilization pond with the aim that the level of wastewater produced can be reduced efficiently and naturally. But the biggest problem is, they have is in the environmental aspect of the generated wastewater because it contains cyanide compounds that have  potential to pollute the Rambung River. In addition, physical factors and the dimensions of the pond also have a major influence on the industrial wastewater treatment of PT Sari Tani Sumatra. To prevent pollution, an evaluation was carried out in the form of an analysis of the discharge and wastewater content, as well as an analysis of the dimensions of the pond. From the evaluation results, there is a calculation of the discharge water discharge reaching 500 m3/day with the wastewater content dominated by BOD and Cyanide. Furthermore, in the analysis of the dimensions of the pond, there are 2 out of 9 ponds that have problems due to increasing the level of wastewater, even though the detention time and depth still meet the design criteria for the dimensions of the pond. In order to obtain optimal WWTP processing, it is necessary to recommend recommendations from the evaluation results.